Giant is different: Size effects and the nature of macromolecules. (March 2020) - Zhang, Wen-Bin; Cheng, Stephen Z.D.
Highlights: Size effects are fundamental to macromolecular science. Increasing molecular size allows for increasing complexity and the synergistic effects between components result in emergent properties. The behaviors of macromolecules (or macromolecular systems) are governed by characteristic physical rules at each different scale of length, time, and energy. Size does matter and giant is different. Abstract: A century after Staudinger's Macromolecular Hypothesis, macromolecular science is entering a new era. In this perspective, we discuss size effects and the nature of macromolecules. With increasing molecular size, the complexity increases dramatically in terms of both primary chemical structure and assembled physical structure, as exemplified by the information-bearing molecules like DNA, RNA, and proteins. The collective and cooperative interaction, as governed by different physical rules at different scales of length, time, and energy, leads to emergent properties of a macromolecule beyond the sum of its components and this is why size does matter. The increasingly open and inclusive macromolecular science calls for a multi-interdisciplinary forum for such studies and this is where Giant could make a big difference with a unified and updated perspective on the nature of macromolecules.